Model Implementasi Spiritual Mindfulness untuk Penguatan Mental Health Remaja di Sekolah Islam - Minhatin Afiyah; Moh Milladun Hakimin 'Alim; Abdullah Qohi (Pascasarjana Universitas Qomaruddin, 2026)
This study aims to analyze the implementation model of spiritual mindfulness in strengthening adolescent mental health within Islamic secondary schools. The research employs a qualitative approach with a multiple case study design conducted at two Islamic high schools in Gresik, Indonesia. Data were collected through participatory observation, in-depth interviews, and document analysis, and analyzed thematically using iterative and comparative procedures. The findings reveal two distinct yet complementary models of spiritual mindfulness implementation. The first model, identified as a ritual-collective approach, emphasizes structured and consistent communal religious practices such as dhikr, congregational prayer, and spiritual habituation to create emotional stability prior to academic activities. The second model, categorized as a reflective-dialogical approach, integrates mentoring programs and spiritual counseling sessions that facilitate cognitive reappraisal and personal meaning-making processes among students. Drawing upon emotion regulation theory and religious coping frameworks, the study demonstrates that spiritual mindfulness functions as a form of religious cognitive reappraisal that enhances emotional regulation, resilience, and psychological well-being among adolescents. From a Sufi perspective, these practices correspond to the concepts of muraqabah, muhasabah, and tazkiyat al-nafs, which cultivate self-awareness and inner tranquility. The novelty of this research lies in proposing an integrative model of spiritual mindfulness rooted in Islamic epistemology while remaining theoretically coherent with contemporary psychological frameworks, offering a preventive strategy for adolescent mental health development in Islamic educational institutions.